(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The gig economy has emerged as a transformative force in contemporary labor markets, reshaping the dynamics of corporate hiring and individual employment preferences. This study delves into the factors that underpin the perceived importance given to the gig economy, encompassing both cost and non-cost considerations. Through rigorous analysis, the research reveals several pivotal findings.Cost-related factors play a crucial role in shaping the significance of gig hiring. Organizations that prioritize cost benefits, such as overall savings and high acquisition costs, are more likely to attribute greater importance to gig workers. The potential for statutory levy exemptions further amplifies this trend, emphasizing the importance of regulatory considerations. Non-cost factors exert a significant influence on the importance assigned to the gig economy. Notably, the emphasis on task-based gig roles stands out as a key driver, reflecting the value placed on flexibility and task-specific expertise. Skill-based roles, while relevant, exhibit a slight negative impact, suggesting nuanced concerns among organizations.The study also underscores the multifaceted nature of non-cost considerations. Non-core roles have a minimal positive influence on importance, indicating their supplementary nature in organizational strategies. In contrast, support service roles exhibit a slight negative impact, hinting at considerations related to stability and quality of service.The perception of gig workers demanding higher salaries compared to full-time counterparts negatively influences importance, but this effect is mitigated when cost-effectiveness is taken into account.Overall, this study provides a comprehensive understanding of the factors influencing the importance given to the gig economy in corporate hiring. It emphasizes the intricate interplay between cost and non-cost elements, highlighting the need for organizations to adopt a holistic approach in navigating the evolving landscape of modern work arrangements.